2019
DOI: 10.1111/idj.12406
|View full text |Cite
|
Sign up to set email alerts
|

Is there enough evidence that mouthguards do not affect athletic performance? A systematic literature review

Abstract: This systematic review provides evidence for sports professionals to advocate the use of custom-made mouthguards to prevent injury, and these devices do not impair performance. The scientific evidence should be interpreted carefully because there is a great variability in outcome measures and lack of important methodological details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
14
0
2
Order By: Relevance
“…Further research is warranted to assess the objective effect of custom‐made occlusal‐accommodated mouthguards on various athletic performance domains, including sprint swimming, vertical jumps in the water, precision/velocity on passing/shooting the ball, and muscular strength. The present results corroborate the lack of evidence about whether custom‐made mouthguards interfere with or improve an athlete's performance 16 . Consequently, oral appliances or occlusal‐accommodated mouthguards should not be recommended to improve athletic performance in the absence of high‐quality evidence to support this claim 37 …”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Further research is warranted to assess the objective effect of custom‐made occlusal‐accommodated mouthguards on various athletic performance domains, including sprint swimming, vertical jumps in the water, precision/velocity on passing/shooting the ball, and muscular strength. The present results corroborate the lack of evidence about whether custom‐made mouthguards interfere with or improve an athlete's performance 16 . Consequently, oral appliances or occlusal‐accommodated mouthguards should not be recommended to improve athletic performance in the absence of high‐quality evidence to support this claim 37 …”
Section: Discussionsupporting
confidence: 78%
“…13 Custom-made mouthguards provide superior fit and retention, offer greater protection, and interfere less with speech and breathing than the other types of mouthguard. 7,[13][14][15] Although a recent review indicated that custom-made mouthguards do not impair athletic performance, 16 the optimal mouthguard design for water polo players is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the link between specific occlusion condition and body posture better, investigations were initiated on immediate effects of different occlusion conditions of the body posture [4,[9][10][11][16][17][18][19][20][21][22][23][24][25][26][27]. In a pilot study, März et al [10] could demonstrate that the fleche lombaire and the Kyphotic angle changed slightly with a symmetrical occlusal interference with cotton rolls compared to habitual bite position.…”
Section: Introductionmentioning
confidence: 99%